LOW DOSE BATH FROM IMPT VS. IMXT FOR THE PELVIC AREA WHEN TREATING ADVANCED PROSTATE CANCER - Navrátil, Matěj; Vondráček, Vladimír; Andrlík, Michal; Kubeš, Jiří; Rosina, Jozef; Grebenyuk, Alexander (Radiation protection dosimetry, 2019)
Twenty (10 intensity-modulated proton therapy (IMPT) and 10 intensity-modulated x-ray therapy (IMXT) treatment plans for patients with advanced prostate carcinoma were compared in this study. All chosen patients were indicated for prostate and pelvic lymph nodes irradiation using simultaneous integrated boost technique. These patients represent typical specimen for this diagnose. IMPT irradiates just half of the tissue volume with a low dose (up to 10 cobalt gray equivalent) compared to IMXT without compromise in target volumes coverage and in this way reduces the risk of secondary cancer development or other possible complications.
Keywords: Organs at Risk; pánev; Radiotherapy Dosage; rentgenová terapie; celková dávka radioterapie; mužské pohlaví; nádory prostaty; Lymph Nodes; protonová terapie; Radiotherapy, Intensity-Modulated; X-Ray Therapy; Prostatic Neoplasms; Humans; radioterapie s modulovanou intenzitou; plánování radioterapie pomocí počítače; lymfatické uzliny; Proton Therapy; Pelvis; kritické orgány; lidé; Male; Radiotherapy Planning, Computer-Assisted